Eficácia da educação conscientizadora no controle da hipertensão arterial sistêmica - Cesarino, Cláudia Bernardi (2006)
Introduction: The patients compliance as well as an adequate blood pressure control are the major challenges in the treatment of hypertension. Objective: The purpose of this study was to observe the efficacy of an education program carried out by the nurse by means of a conscious pedagogical methodology in the blood pressure control, in the treatment compliance with a non-pharmacological therapy as well as in the frequency to examinations in the hypertension service. Casuistics and Method: Two groups of hypertensive individual were studied: the control group that attended the hypertension routine service; and the study group that besides the service took part in educational activities based on Paulo Freire s pedagogical methodology carried out by the nurse. Blood pressure was indirecty measured in both groups, biweekly; the control group was let off after examinations, and the study group referred to the educational activities. These were held during 12 months, in a total of 23 meetings, and at-home visits were accomplished for both groups after 24 months of the education program starting period. Total cholesterol and fractions (HDL, LDL, VLDL), triglycerides, ghycemia, sodium-potassium at the last 24-hour urine tests were collected, quarterly. Results: It was observed that the blood pressure was around normal level in the study group; the body mass index values, tryglicerides and urine-sodium were lowered. Some changes in the non-pharmacological therapy was also observed such as: a better understanding about the disease, smoking was quitted and the frequency in physical activities. There were no significant changes in both groups in relation to ethylism and other metabolic parameters. At-home visits, the study group showed adequate blood pressure control in 95.69%, where as the control group, 34.8% (p<0.05). There was a significant difference between the two groups in relation to the frequency to the examinations in the hypertension service since no patients of the study group abandoned the follow-up, whereas 21.70% of the control group did (p<0.05). Conclusion: This education program has got the study group patients aware in relation to the treatment since it was taken seriously and better results were showed such as: adequate blood pressure control; the examination compliance in the hypertension service as well as the non-pharmacological therapy. Therefore, this study is likely to contribute to further changes in hypertensive patient s education.